Recent autochthonous cases of leishmaniasis in residents of the Republic of Dagestan, Russian Federation. (September 2019) - Nagorny, Sergey Andreevich; Ermakova, Larisa Alexandrovna; Golovchenko, Natalia Vladimirovna; Pshenichnaya, Natalia Yurievna; Zhuravlev, Andrey Sergeevich; Di Muccio, Trentina; Gradoni, Luigi
Highlights: The last record of human leishmaniasis from Dagestan was reported in 1938. Locally-acquired Leishmania disease was diagnosed in 2 patients from Dagestan. Problems in notification and timely diagnosis and treatment may occur in the future. Abstract: Eighty years after the last published record of human leishmaniasis from Dagestan, Russian Federation, we report two recent cases which were most probably acquired locally: one case of visceral leishmaniasis in a 2-year old child, and one cutaneous leishmaniasis case in a 39-year-old man co-infected with HIV, both resident in Dagestan.